Role of poly(ADP-ribose) polymerase-1 in the removal of UV-induced DNA lesions by nucleotide excision repair - Robu, Mihaela (National Academy of Sciences, 2013)
Among the earliest responses of mammalian cells to DNA damage is catalytic activation of a nuclear enzyme poly(ADP-ribose) polymerase-1 (PARP-1). Activated PARP-1 forms the polymers of ADP-ribose (pADPr or PAR) that posttranslationally modify its target proteins, such as PARP-1 and DNA repair–related proteins. Although this metabolism is known to be implicated in other repair pathways, here we show its role in the versatile nucleotide excision repair pathway (NER) that removes a variety of DNA damages including those induced by UV. We show that PARP inhibition or specific depletion of PARP-1 decreases the efficiency of removal of UV-induced DNA damage from human skin fibroblasts or mouse epidermis. Using NER-proficient and -deficient cells and in vitro PARP-1 assays, we show that damaged DNA-binding protein 2 (DDB2), a key lesion recognition protein of the global genomic subpathway of NER (GG-NER), associates with PARP-1 in the vicinity of UV-damaged chromatin, stimulates its catalytic activity, and is modified by pADPr. PARP inhibition abolishes UV-induced interaction of DDB2 with PARP-1 or xeroderma pigmentosum group C (XPC) and also decreases localization of XPC to UV-damaged DNA, which is a key step that leads to downstream events in GG-NER. Thus, PARP-1 collaborates with DDB2 to increase the efficiency of the lesion recognition step of GG-NER.